MANFAAT PEMANASAN STATIS DAN DINAMIS SERTA PENDINGINAN BAGI SISWA DI SD NEGERI 101740 TANJUNG SELAMAT - Ginting, Refa Ivana Br; Agustina , Citra; Aritonang , Kornelis; Pakpahan , Anjeli Agustina; Sembiring , Heka Maya Sari Br (ASOSIASI IDEBAHASA KEPRI, 2025)
This study examines the impact and benefits of warm-up (static and dynamic) and cool-down activities to prevent injuries during physical exercise. Emphasizing their role in enhancing circulation and body readiness, the program—titled